Technologically-rich computational activities in K–12 education: a systematic review of constructivist and constructionist interventions. - Possaghi, Isabella; Papavlasopoulou, Sofia (Behaviour & Information Technology, 2026)
The interest in computing learning activities is continuously increasing, keeping pace with the evolution of educational technologies. This rise in engagement is evident within approaches grounded in constructivism and constructionism, which provide an ideal setting for the spectrum of skills, literacies, and competencies that global initiatives capitalise on in K–12 education. Due to recent advancements in technology and societal changes, we are addressing the need for an updated perspective focussed on designing and implementing computational activities. To achieve this, we have analysed forty-six peer-reviewed empirical studies from the last decade to summarise technology-supported learning strategies' current direction and future potential. The main findings describe programming software and IoT as the preferred digital tools, often presented in novel combinations, extensions, and contextualisations. Implementation primarily occurs within the domain of computer science but exhibits a high degree of interdisciplinarity. Furthermore, there is an increase in activities referring to real-life scenarios, encouraging learners to develop computational skills beyond the classroom and expand their digital awareness through interaction with emerging technologies. We leverage these trends and significant patterns by proposing a summary of focal points for future research and practice, with a focus on activity design.